Dīwān-i Mukhliṣ-i Kāshānī - Kāshānī, Mukhliṣ (Miras Maktoob, ISBN: 9789004365452., 2019)
Persian poetry of the pre-modern era is divided into three successive styles, each belonging to a different period: Khurāsānī, ʿIrāqī and Hindī. The Hindī style is called such because in Safavid times, during which it developed, poets no longer enjoyed the shah's patronage so that many of them went to India, where Persian poetry had flourished since Ghaznavid times (11th-12th cent.). The Hindī style is often regarded as being of a lesser kind than the Khurāsānī or ʿIrāqī ones, but has the merit of having put a halt to the decline that Persian poetry was suffering from at the time and also, by its accessible language and subject matter, of having brought poetry within reach of the ordinary man. The Hindī style of those who never went to India is commonly described as 'Iṣfahānī'. Mukhliṣ Kāshānī's (d. 1150/1737) poetry is Hindī in the Iṣfahānī variant and is published here for the very first time.